Status and Trends of the Application of Resilient Urban Governance Considering the Current State of Resilient City Government in Changsha as an Example - Haibo Jiang; Xiaoque Luo; Yonghua Gong; Yongshen Li; Wu Zhao (Buildings)
Currently, cities’ security vulnerabilities are diverse, complex, and interrelated, making the building of resilient cities an essential requirement to deal with these risks and ensure the long-term growth of cities. China is making headway toward resilient urban governance, as evidenced by a focus on ecological hazards and widespread application in urban planning, social development, and other areas. However, as urbanization continues, traditional governance techniques confront the challenge of “lack of clarity, inadequate execution, and slow response.” To address these difficulties, this work introduces a novel dual-core-driven model of ‘defense system + organism’. By analyzing the main urban safety risks currently present in Changsha City and employing literature synthesis, field surveys and interviews, and comparative analysis, it investigates the application status of resilient urban governance and empirically constructs a ‘three-dimensional fifteen-wing’ governance system, achieving a transition from passive defense to an intelligent–adaptive governance paradigm.